Exploring the Adsorption Properties of Zeolite in a New Skin Care Formulation - Massimo Pesando; Veronica Bolzon; Michela Bulfoni; Alessandro Nencioni; Emanuele Nencioni (Cosmetics, 2022)
Introduction: Zeolites are natural or synthetic aluminosilicates, characterized by a regular and microporous crystalline structure that plays a particularly active role in neutralizing free radicals, screening UV rays and in the adsorption of toxins and heavy metals. Skin is one of the main areas for the accumulation of toxic substances released by environmental pollutants. The biological scavenger activity of zeolite opens a wide spectrum of applications in cosmetics and dermatology. Up to now, there is little evidence related to the use of natural zeolite in cosmetics. Aim: The purpose of this work was to evaluate the ability of zeolite to retain heavy metals in a new skin care formulation, in order to provide a proof of principle of its employment in the field of cosmetics. Materials and Methods: Taking the advantages of spiked samples, we studied the in vitro adsorption properties of zeolite in a new skin care formulation. The removal capacities of Cadmium, Lead, Chromium, Nickel and Cobalt were studied, using the inductively coupled plasma optical emission spectrometry (ICP-OES). First of all, the better concentration of zeolite was defined, testing two different proportions of zeolite, from 1% to 3%, keeping all other components constant. Then, on the 3% formulation, the adsorption properties of each single metal were measured. Results and Conclusions: Our preliminary study demonstrated the selectivity of zeolite in retaining Cadmium (p < 0.0001), Nickel (p = 0.026), in a 3% zeolite-based formulation. This work provides a proof of principle of zeolite employment in the field of cosmetics. Based on the data collected, our work provides a scientific proof of principle of zeolite employment in the field of cosmetics. New and extensive research will be needed to explore all the potential benefits of zeolite.